(NpRAKTIKUM PO SPEKTROSKOPII (B:s (Nu^EBNOE POSOBIE (B/s - (NlEBEDEW(B, (Nw(B.(Nw(B.s; (NlEW[IN(B, (NlEONID wADIMOWI^s; (NlEW[IN(B, (NlEONID wADIMOWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1976)
(NsPISKI LIT(B. (NW KONCE GLAWs
Keywords: (NsPEKTROSKOPIQs